How are social media changing the lives of young people? - Iroda Yormamatovna Beknazarova; Maxliyo Muxtorjon-qizi Qilicheva (Science and Education, 2026)
This article analyses the positive and negative impacts of social media on the lives of young people. In particular, it highlights problems such as young people becoming absorbed in virtual life, distancing themselves from reading books, disruption of sleep patterns, negative effects on mental health, addiction to useless content, and cyberbullying. At the same time, the article also shows the positive aspects of social media in terms of education, learning foreign languages, and communicating with people who are far away. Solutions such as teaching young people to use social media in moderation, promoting reading habits, and strengthening parental supervision are proposed.